The Influence of Integrating Multicultural and Ethical Values on the Effectiveness of Digital-Based Islamic Religious Education Learning - Rapiko; M. Hurmaini; Kasful Anwar; Kartubi (Soshum: Jurnal Sosial dan Humaniora, 2026)
This study aims to analyse the influence of multicultural and ethical values integration on the effectiveness of digital-based Islamic Religious Education (PAI) learning at UIN Jambi. The primary objective is to determine how these values contribute to shaping tolerant and responsible student behaviour within a digital landscape often marked by polarisation. A quantitative research design was employed, utilising regression analysis to test the correlation between value-based pedagogy and learning outcomes. The population consisted of 310 sixth-semester students, with a representative sample selected via Slovin’s formula. The findings indicate that multicultural values significantly foster tolerance and appreciation for intellectual diversity, particularly in the study of Islamic jurisprudence, while ethical values promote academic honesty and responsible technology use. The study’s novelty is established through its empirical evidence that the integration of these specific values accounts for a substantial 61.8% of the variance in digital learning effectiveness. This study provides empirical evidence from Islamic higher education on how multicultural and ethical value integration predicts digital learning effectiveness. Despite these effective outcomes, the results suggest that further improvements are required in student interaction and assessment strategies. The findings suggest that value-embedded digital pedagogy is essential for developing technologically competent and ethically grounded graduates.